Kehidupan Multikultural di Kota Medan: Dinamika, Tantangan, dan Peluang - Damanik, Fritz Hotman Syahmahita (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
Medan's multiculturalism epitomizes its unique complexity, blending diverse ethnicities, religions, and traditions as North Sumatra's economic and cultural nucleus. This study delves into Medan's multifaceted multicultural life, encompassing its historical narrative, economic dynamism, and globalization's repercussions. Employing a qualitative descriptive approach grounded in literature, the research underscores Medan's historical significance as a cosmopolitan and metropolitan center, shaped by international trade and Dutch colonialism. The city's diverse populace, including Batak, Malay, Javanese, and Chinese communities, enriches its cultural tapestry, evolving continually. Economic dynamics illuminate how ethnic diversity fuels Medan's prosperity, fostering unique social bonds amidst trade and industry. Amidst globalization's onslaught, Medan navigates technological shifts, communication advancements, and human mobility changes, confronting both challenges and opportunities. Understanding Medan's multicultural life necessitates grappling with these global dynamics. This research sheds light on Medan's resilience and adaptability in the face of rapid globalization, offering insights into the intricate interplay between tradition and modernity in this vibrant city.